Aplikasi Pengolahan Presensi Perkuliahan Dengan Metode Prototype di STMIK Asia Malang (LP2M INSTITUT TEKNOLOGI DAN BISNIS ASIA MALANG, 2018)
Absenteeism system by using present technology can be applied in processing the absenteeism of the student of STMIK Asia Malang, where student absenteeism recap used in STMIK Asia Malang at the moment is carried out conventionally. The negative effects of absenteeism recapitulation conventionally are vulnerable to students who like to absent and entrusted the absence to someone. It is because the lecturer sometimes cannot oversee directly the presence of students in large numbers. Therefore a system is designed in order that student absenteeism processing in STMIK Asia Malang can be more effective. System design used in this journal is using prototype method. The results of this system are able to process data on the system and able to do absenteeism data recording.